2021
DOI: 10.1111/fcsr.12414
|View full text |Cite
|
Sign up to set email alerts
|

Association between Financial Education, Affective and Cognitive Financial Knowledge, and Financial Behavior

Abstract: Using data from the 2018 National Financial Capability Study, this articled examined the relationship between financial education participation and affective and cognitive financial knowledge. Involvement in financial education yielded statistically significant associations between affective and cognitive domains. The results showed that participation in financial education was associated with both cognitive and affective financial knowledge as well as long‐term financial behavior. The results supported the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As limited research has investigated how perceptions and financial behaviors differ based on marital status and gender, this study aims to examine the relationship between financial perceptions and financial behaviors across four marital/gender groups. In particular, using nationally representative data, this study focuses on how marital status and gender play a role in practicing healthy financial behaviors (Delgadillo & Lee, 2021;Henager & Cude, 2016;Robb & Woodyard, 2011;Wagner & Walstad, 2019;Xiao et al, 2014). Based on the theory of planned behavior and previous literature, we present the following two hypotheses:…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…As limited research has investigated how perceptions and financial behaviors differ based on marital status and gender, this study aims to examine the relationship between financial perceptions and financial behaviors across four marital/gender groups. In particular, using nationally representative data, this study focuses on how marital status and gender play a role in practicing healthy financial behaviors (Delgadillo & Lee, 2021;Henager & Cude, 2016;Robb & Woodyard, 2011;Wagner & Walstad, 2019;Xiao et al, 2014). Based on the theory of planned behavior and previous literature, we present the following two hypotheses:…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…It has been found that financial knowledge is linked to both short‐term and long‐term financial behaviors (Coskuner, 2016; Delgadillo & Lee, 2021; Henager & Cude, 2016; Kim et al., 2019; Robb & Woodyard, 2011; Xiao et al., 2014). For example, those who expressed a higher level of financial knowledge were more likely to have a retirement plan (Lusardi et al., 2017).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found a strong link between financial knowledge and financial behavior (Coskuner, 2016;Perry & Morris, 2005;Robb & Woodyard, 2011;Xiao et al, 2014). Previous research has found strong links between financial knowledge and both short-and long-term financial behaviors (Delgadillo & Lee, 2021;Henager & Cude, 2016). Previous research has also distinguished between the impact of subjective and objective financial knowledge on financial behaviors.…”
Section: Financial Behaviour Financial Experience and Financial Satis...mentioning
confidence: 99%